DESIGN AND CONSTRUCTION OF A POINT OF SALE INFORMATION SYSTEM FOR AYAM BAKAR B-JO - Arga Agung Wiradika; Rikip Ginanjar (IT for Society, 2022)
Ayam Bakar B-JO is a business thatwas just started in mid-August that requiressystem assistance to manage transaction data,recap transaction data, so that it can make salesreports with transaction details that can be doneautomatically by the system, so that the businessowner can ease the work of the business owner.who must record transactions manually toperform manual calculations of profits.Therefore, a Point of Sale Information Systemwas created for B-JO Grilled Chicken, toovercome the problems experienced by businessowners. With the application of this point of saleinformation system, it is hoped that businessowners can overcome these problems withouthuman error or other things.